Public Policies and Children’s Rights: a reflection from the ethnic-racial perspective - Anete Abramowicz; Fabiana de Oliveira (Zero-a-seis, 2017)
Despite the fact that in recent years we have been open to discussing race-related issues in Brazil, bringing about considerable changes in the contemporary debate, discrimination related to race is still a structural variable in our reality, and education shows this racial inequality in its educational indicators and in the micropolitics of each kindergarten. The black and small children suffer a double social inequality: they are small and black. Through this reflexive essay we seek to discuss issues related to public policies and the rights of black children to education. The relevance for the development of the work is based on the smallness of studies involving public policies, education and childhood from the age and race in Brazil.